The Leadership Role of The Director of The Islamic Boarding School in Developing a Culture of Quality at Trensains Muhammadiyah Senior High School, Sragen - Fitriana Laila Nur Rohmah; Chusniatun Chusniatun (MASI Mandiri Edukasi, 2026)
The role of a leader is an important point that needs to be considered for the organization to be implemented effectively, including in the development of a quality culture. This study aims to describe the leadership role of the Islamic boarding school director in developing a quality culture at SMA Trensains Muhammadiyah Sragen, along with the challenges and solutions. This study is classified as field research with a phenomenological approach. Data collection techniques through observation, interviews, and documentation were then analyzed in three steps: data reduction, data presentation, and conclusion. Meanwhile, the validity of the data in this study was tested through technical triangulation and source triangulation. The results of the study revealed that the director plays an important role in developing a quality culture at SMA Trensains Muhammadiyah Sragen. Efforts made include ensuring the development of a quality culture in line with the school's vision and mission, building a good environment, establishing a unified curriculum, managing resources and budget optimally, establishing good communication between asatidz/ah, and building cooperative relationships with parents and the surrounding community. As for the challenges and solutions, first, in addressing the lack of teacher competency, the director seeks a language study forum. Second, in addressing the public stigma regarding expensive schools, the director developed a productive endowment managed by Lazismu Trensains.